Speech Disfluency and Autism in Schools: Identifying Needs and Providing Support to SLPs. (30th June 2015) - Scott, Kathleen Scaler; Block, Sheri; Reeves, Nina; Nelson, Sarah
Abstract: In recent years, there has been a gradually increasing body of literature documenting patterns of disfluency in samples of children on the autism spectrum (see Scaler Scott, Tetnowski, Flaitz, &Yaruss, 2014, for review). This study discusses the results of two surveys. The first survey, discussing 395 students, demonstrates the identification of students with autism and disfluency among school-based speech-language pathologists (SLPs) in three areas of the United States of America. This increased documentation suggests growing concern about treatment methods for disfluencies within this population. The second part of this study discusses a pilot training conducted with one school district in the United States. SLPs were surveyed regarding their knowledge and confidence level in identifying and working with fluency disorders in students with autism. The survey was conducted before and after a training seminar on fluency disorders in children with autism. Three months after training, the SLPs in that district were resurveyed to determine the numbers of cases identified and their comfort level with identifying, evaluating, and treating disfluencies. Despite increases in comfort following training, participants indicated that they were less than comfortable with procedures of referral and treatment. Implications for future SLP training will be discussed.